STUDI PENGEMBANGAN POTENSI DESA UNTUK MENINGKATKAN PENDAPATAN ASLI DESA ROKAN KOTO RUANG KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU TAHUN 2012-2015 - Lexsi Fanfair; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Rokan Koto Ruang Village does have a lot of potential and some of the potential of the village in Rokan Koto Ruang Village can be developed through Village-Owned Enterprises, such as agricultural, plantation, fisheries, livestock, forest product management and tourism. With good professional management and management, the village potential can be maximally developed to improve community welfare. The Rokan Koto Ruang Village-Owned Enterprise is owned by the community and it is seen that the growth of business results generated by the Rokan Koto Ruang Desa-Owned Business Entity is not beneficial for the Village and cannot be utilized properly.The purpose of this study is first, knowing the potential of the village can be developed by the village government of Rokan Koto Ruang. Secondly, to find out the Factors that are the obstacles to the Village Government in developing village potential. The type of research that I use in this case is a type of descriptive research with qualitative analysis methods. The location of this research was conducted in Rokan Koto Ruang Village due to having a lot of potential that could be developed such as agriculture, plantation, fisheries, livestock, mining, forestry, and tourism. Data collection techniques that the author did by way of observation, interviews and documentation. While data analysis is done by qualitative analysis.The results of this study indicate that Rokan Koto Ruang Village has tremendous natural resource potential in the form of tourism potential, agriculture, plantations, livestock, and superior products as a result of the creativity of the community of Rokan Koto Ruang Village. Tourism potential that can be developed in Rokan Koto Ruang Village, with the creativity of the managers of BUMDes and the Village Government, tourism villages can be realized as long as the Village Government must be committed to developing this tourism potential and must improve Human Resources for the welfare of the community. But in developing tourism in Rokan Village, Koto Ruang also faces many obstacles. The main problems are infrastructure, promotion / information media and transportation. In addition, business management of tourist attractions that are still not developed in accordance with the wishes of tourists. Keywords: Village Government, Village Potential, Village AutonomyKeywords: Potential Record Of The Village, Village Potential Development, Village Tourism.